2009
DOI: 10.1177/0022034509342851
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Luting Material Filler Content on Post Cementation

Abstract: Luting of fiber posts to intra-radicular dentin represents the worst-case scenario in terms of control of polymerization shrinkage. This study tested the hypothesis that filler content of resin cements does not influence luting of fiber posts to intra-radicular dentin, by assaying polymerization stress, push-out bond strength, and nanoleakage expression. The polymerization stress of experimental cements containing 10%, 30%, 50%, or 70% in filler content was investigated. Post spaces were prepared in endodontic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 24 publications
1
39
0
7
Order By: Relevance
“…All groups in this study showed higher values in the cervical third, while the lowest were found in apical third. These results are consistent with other studies that have revealed regional differences in bond strength (5,16).…”
Section: Discussionsupporting
confidence: 93%
“…All groups in this study showed higher values in the cervical third, while the lowest were found in apical third. These results are consistent with other studies that have revealed regional differences in bond strength (5,16).…”
Section: Discussionsupporting
confidence: 93%
“…Even though composite resin core material generally have more filler and, therefore, higher strength than resin cements, polymerization shrinkage stress is higher with 70% filler than that with 10% filler. 30 This may seem counterintuitive to most dentists, but the objective is to employ a technique that compensates for the inherent deficiencies of some types of material and capitalizes on them without becoming clinically cumbersome, time-consuming, or with the integration of outside laboratory fees.…”
Section: Discussionmentioning
confidence: 99%
“…Ferrari et al [11] presented that, when the filler load is increased, the polymerization stress will increase due to decrease in the bonding strength. The tooth/restoration interface can suffer long-term degradation due to the action of water, temperature changes, and mechanical loading [12][13][14] which lead to failure over time [13,15,16].…”
Section: Introductionmentioning
confidence: 99%